Nutrition and oral health - Gondivkar, Shailesh M.; Gadbail, Amol R.; Gondivkar, Rima S.; Sarode, Sachin C.; Sarode, Gargi S.; Patil, Shankargouda; Awan, Kamran H. (Disease-a-month, 2019)
To maintain health, the human body needs daily nourishment in the form of carbohydrates, proteins and minerals. The associations between oral health conditions, dietary practices and nutritional status, and general health status are complex with many interrelating factors. Inadequate nutrition can affect the oral health including dental caries, periodontal diseases, diseases of oralmucosa and infectious diseases. Compromised oral health can alter food choices and negatively impact food intake leading to suboptimal nutritional status which can lead to chronic systemic diseases. Recognizing and treating oral health and nutrition problems are important in improving the health and quality of life.